Efektifitas Praktikum Multimedia Struktur Atom dalam Mengatasi Miskonsepsi Kimia Anorganik Mahasiswa - Suyanti Dwi Retno; Sugyarto Sugyarto (Jurnal Pendidikan dan Kebudayaan, 2011)
This research aims to determine shell atomic energy related How finding Rydberg Constanta. This research was be held on Deparment of Chemistry Medan State University. Through Anorganic teaching and learning integrated with multimedia practikum, several misconception in atomic structure atomic has been overcome. The Efectivity of Multimedia Practicum in Atomic Structure for Overcoming Students Misconception Anorganic Chemistry. This research try to present discussion direct material in Inorganic Chemistry include atomic structure. The result of this research shows that there is skill student improving in learning atomic structure because of misconception trhough Rydbergâ€™s role and occuring hydrogeen spectrum from the fourth step.Â ABSTRAKTujuan penelitian ini dimaksudkan untuk memperoleh informasi tentang kemampuan inquiry mahasiswa dalam menelusuri bagaimana para pakar kimiawan menemukan tetapan Rydberg sehingga tidak terjadi miskonsepsi dalam memahami struktur atom khususnya dan Kimia Anorganik pada umumnya. Penelitian ini dilakukan di Jurusan Kimia FMIPA UNIMED dengan mengintegrasikan praktikum multimedia dan pembelajaran Kimia Anorganik. Hasil penelitian menunjukkan.terdapat peningkatan pemahaman mahasiswa dalam mempelajari struktur atom karena miskonsepsi terhadap tetapan Rydberg dan pembentukan spektrum Hidrogen dari ke empat ligan teratasi.